Novel forms for the expression of aspect in heritage Greek across majority languages. - Vasiliki Rizou; Despina Papadopoulou; Onur Özsoy; Artemis Alexiadou (PLoS ONE)
This paper investigates, on the one hand, which verbal features are re-organized in heritage grammars and, on the other hand, the production of novel non-canonical forms for the expression of verbal aspect by Greek heritage speakers in Germany and the US compared to monolingually-raised speakers of Modern Greek (henceforth Greek). As aspect cannot be seen in isolation from other morphological features such as voice, tense, and phi-features, the analysis of the novel forms is conducted under the prism of the verbal complex. The results indicate that φ-features and aspect seem to be the most re-organized elements encoded in Greek verbs and, furthermore, that heritage speaker groups differ significantly from monolingually-raised controls in terms of the production of novel morphological forms, demonstrating that heritage speakers, especially those in the US, face difficulties with the morpho-phonological adjustments needed to be built in verbal forms.